Postpartum Invasive Group A Streptococcal Disease in the Modern Era. (31st December 2008) - Aronoff, David M.; Mulla, Zuber D.
Abstract : To describe the clinical features of individuals hospitalized for postpartum invasive group A Streptococcus (GAS) infection, a retrospective, population-based study of hospitalized patients in the state of Florida was conducted. Cases of postpartum invasive GAS infection (occurring within 42 days of delivery) were compared to women with other manifestations of invasive GAS disease with respect to their age at the time of admission. Four cases of postpartum invasive GAS infection were detected in this population, yielding a prevalence of 1.6% (4/257) of postpartum disease in this invasive GAS infection database. Patients presented a median of 4 days (mean of 9 days) after delivery with signs and symptoms of infection. Three cases were complicated by bacteremia and one patient had streptococcal toxic shock syndrome. Each patient received multiple antibiotics and survived. No patients received intravenous immunoglobulin. For comparison, a secondary retrospective investigation of a large hospital discharge dataset obtained from the Florida Agency for Health Care Administration was assessed for patients with puerperal GAS infections. This method yielded an additional three cases, whose clinical and demographic characteristics were summarized. These data highlight that postpartum invasive GAS infection continues to complicate pregnancy, though the frequency has decreased markedly over the past century.